Protection Properties of He-Ne Laser (632.8 nm) Against UV-light (253.7 nm) On the Lymphocytes Blood Cellsand Its DNA. - Taha, Jenan H.; AL-Ani, Fikher S.; AL-Siaidy, Wijdan F. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: He-Ne laser (632.8 nm) pre-irradiation may lead to modulate the damaging effects of ionizing radiation and decreasing in radiation damage on cells, by the induction of antioxidant defence mechanisms and accelerated the repair.Objective: To study the protection properties of He-Ne laser (632.8 nm) pre-irradiation against UV light (253.7 nm) damage on human lymphocyte blood cells and its DNA.Subject & Methods: 27 samples were processed only for lymphocyte blood cells separation, while a 45 samples for the extracted DNA from lymphocyte. The total of 72 sampleswere employed to evaluate the influence of He-Ne laser pre- irradiation against UV-light.Results: The results showed that He-Ne laser (632.8 nm) pre-irradiation on human lymphocyte blood cells and its DNA leads to a decrease in the damage which caused by UV light (253.7 nm) irradiation.Conclusion:The magnitude of protection depends on the He-Ne laser pre-exposure doses. A higher survival percentage of lymphocyte blood cells and its DNA occurred with low He-Ne laser dose.